Nicking enzyme-assisted signal-amplifiable Hg2+ detection using upconversion nanoparticles - Vijayan, Anjaly N.; Liu, Zhiming; Zhao, Haohan; Zhang, Peng (Analytica chimica acta, 2019)
A highly specific and sensitive isothermal method for mercury detection using DNA-conjugated upconversion nanoparticles is reported. A single-stranded DNA containing thymine bases, used as the Hg2+-capturing element through the formation of thymine-Hg2+-thymine complex, is covalently attached to the NaYF4: Yb3+, Tm3+ nanoparticles. Luminescence resonance energy transfer takes place between the NaYF4: Yb3+, Tm3+ nanoparticles as donor and DNA-intercalating SYBR Green I as the acceptor upon excitation of 980 nm. The sensitivity and selectivity toward Hg2+ are enhanced using the nicking enzyme, Nt. Alwl, which leads to signal amplification. By monitoring the ratio of acceptor emission to a reference peak, the presence of Hg2+ ions are quantitatively determined with a lower detection limit of 0.14 nM, which is much lower than the US Environmental Protection Agency (EPA) limit of Hg2+ in drinking water. We report a highly specific and sensitive isothermal method for Hg2+ ion detection using DNA-conjugated upconversion nanoparticles. [Display omitted] •Hg2+ detection using upconversion nanoparticles with a detection limit lower than US EPA limit of Hg2+ in drinking water.•Selective, sensitive and isothermal method with good reproducibility in complex matrix.•Signal amplification using nicking enzyme makes the detection scheme unique.